2015
DOI: 10.1371/journal.pone.0145695
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Chronic Microdose Lithium Treatment Prevented Memory Loss and Neurohistopathological Changes in a Transgenic Mouse Model of Alzheimer's Disease

Abstract: There is an error within the fourth sentence of the Abstract. The correct sentence is: Transgenic mice (Cg-Tg(PDGFB-APPSwInd)20Lms/2J) and their non-transgenic litter mate genetic controls were treated with lithium carbonate (0.25mg/Kg/day in drinking water) for 16 or 8 months starting at two and ten months of age, respectively.There is an error within the first sentence of the second paragraph of the Results and Discussion section. The correct sentence is: Lithium was administered as lithium carbonate in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
0
10
0
Order By: Relevance
“…Chronic (>15 months) microdose lithium administration has been suggested to stabilize memory impairment in AD patients (Nunes et al, 2013) and prevent neuropathology and cognitive decline in mice and rat models of AD with no observed toxicity (Nunes et al, 2015; Wilson et al, 2017). More recently LISPRO, a new ionic co-crystalized formulation of lithium salicylate and L-proline, has been reported to have improved brain penetrance and a safer pharmacokinetic profile over classical lithium chloride and carbonate salts (Habib et al, 2017).…”
Section: Future Perspectives: Combination Therapies Vs Lithium Treatmentioning
confidence: 99%
“…Chronic (>15 months) microdose lithium administration has been suggested to stabilize memory impairment in AD patients (Nunes et al, 2013) and prevent neuropathology and cognitive decline in mice and rat models of AD with no observed toxicity (Nunes et al, 2015; Wilson et al, 2017). More recently LISPRO, a new ionic co-crystalized formulation of lithium salicylate and L-proline, has been reported to have improved brain penetrance and a safer pharmacokinetic profile over classical lithium chloride and carbonate salts (Habib et al, 2017).…”
Section: Future Perspectives: Combination Therapies Vs Lithium Treatmentioning
confidence: 99%
“…The preservation of neuronal density is a typical characteristic of the treatment with the lithium in low-dose, as we have been observed this effect in the hippocampus of 16-months-old transgenic mice model for AD [ 14 ] and 10-months-old male SAMP-8 [ 13 ] with the chronic treatment with lithium. Also the treatment of ex-vivo hippocampus slices with lithium in low-dose also evidenced the neuroprotection observed in vivo [ 36 ].…”
Section: Discussionmentioning
confidence: 81%
“…Alzheimer’s disease (AD) is still the most important cause of dementia worldwide, but until today that is no cure for this devastating disease. In the last years, our research team showed the beneficial effects of the treatment with microdose lithium for memory maintenance and neuroprotection in a transgenic mice model of AD [ 14 ], but the cellular mechanisms of this low dosage of lithium are still lacking.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations